Pengaruh Brand Image dan Keunggulan Bersaing Terhadap Keputusan Mahasiswa Dalam Memilih Politeknik Hasnur Yang Di Mediasi Oleh Word Of Mouth Positif - Mariyam, Mariyam; Taharuddin, Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
This study aims to examine and deretmine the direct and indirect effect between Brand Image and competitive advantage in the decision to choose Politeknik Hasnur mediated by positive Word of Mouth. This study uses a quantitative research method with an explantory type and uses the SmartPLS data analysis method. By collecting data through distributing questinnaires to second semester and fourth semester Politeknik Hasnur students who are still active    and residing in South Kalimantan  with a sample of 171 respondents. The results of this test prove that Brand Image has no significant effect on the decision to choose Politeknik Hasnur, competitive advantage has a significant effect on the decision to choose Politeknik Hasnur and positive Word of Mouth as mediation also has a significant effect on student decisions in choosing Politeknik Hasnur. Keywords: Brand Image, Competitive  Advantage, Word of Mouth, The Decision to Choose a Politeknik Hasnur